2008
DOI: 10.1002/mrm.21792
|View full text |Cite
|
Sign up to set email alerts
|

Field strength dependence of R1 and R relaxivities of human whole blood to prohance, vasovist, and deoxyhemoglobin

Abstract: This study has measured the longitudinal and transverse (T* 2 ) relaxivity curves for ProHance (Gadoteridol), Vasovist (Gadofosveset) and deoxyhemoglobin at 1.5, 3.0, and 7.0 Tesla. The plots of R 1 versus both contrast agent and deoxyhemoglobin concentration were linear. The plots of R* 2 versus deoxyhemoglobin concentration showed a quadratic dependence. R* 2 versus contrast agent concentration showed a parabolic dependence with a minimum occurring at contrast agent concentrations of approximately 1.5 mM, co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
152
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(169 citation statements)
references
References 23 publications
(39 reference statements)
15
152
2
Order By: Relevance
“…Baseline R 2 * values for the human tumours were lower than those found in the xenografts because of the magnetic field strength dependence of R 2 * relaxivities (Blockley et al, 2008), and also showed less heterogeneity (R 2 * ¼ 7.1 -29.2 s À1 ). The susceptibility-weighted BOLD technique proved to be highly repeatable in human prostate cancer with a wCV of 4.7%.…”
Section: Human Testingmentioning
confidence: 72%
“…Baseline R 2 * values for the human tumours were lower than those found in the xenografts because of the magnetic field strength dependence of R 2 * relaxivities (Blockley et al, 2008), and also showed less heterogeneity (R 2 * ¼ 7.1 -29.2 s À1 ). The susceptibility-weighted BOLD technique proved to be highly repeatable in human prostate cancer with a wCV of 4.7%.…”
Section: Human Testingmentioning
confidence: 72%
“…Despite the fact that HCT is recognised as an important scaling factor for AIF (12), very few studies have investigated its impact on T 1 and T 2 Ã as a function of contrast agent concentration (15,28). The effect of HCT on blood T 1 values has been shown to be linear (33,34), whereas the effect of HCT on blood T 2 and T 2 Ã values has generally been investigated as a function of blood oxygenation (28,35,36). For the first time, the effect of HCT on blood-doped gadodiamide R 2 Ã values was evaluated for a range of HCTs.…”
Section: Discussionmentioning
confidence: 98%
“…In this respect, these results provide evidence against the assumption that the specific nature of the contrast agent might be responsible for the conflicting results. Although Vasovist is based on gadolinium rather than on iron oxide particles as used for most animal studies, it temporarily binds to the blood albumin and also acts as a blood-pool contrast agent (Blockley et al, 2008;Majos et al, 2009;Morton et al, 2006). To which degree interspecies differences and/or influences from anesthesia have a role cannot be answered at this stage.…”
Section: Discussionmentioning
confidence: 99%